2019
DOI: 10.1111/hiv.12781
|View full text |Cite
|
Sign up to set email alerts
|

Dual therapy with renally adjusted lamivudine and dolutegravir: a switch strategy to manage comorbidity and toxicity in older, suppressed patients?

Abstract: Objectives The aim of the study was to evaluate the efficacy of dual therapy with lamivudine (3TC), with dose adjustment for renal function, and dolutegravir (DTG) in a subgroup of patients fully suppressed on treatment who were switched because of concerns about comorbidity and toxicity on their current triple drug regimen. Methods A retrospective evaluation of clinical and pathological parameters from an electronic patient record from a single centre was carried out. Results There were no virological failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 4 publications
3
12
0
3
Order By: Relevance
“…This analysis included 5017 PWH who were reported to be using dolutegravir plus lamivudine. In 20 studies that reported data for sex, the majority of PWH treated with dolutegravir plus lamivudine were male (range, 60-97%) [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. In five of seven studies with reported racial demographics, C 90% of PWH were identified as White [30,32,33,42,43,46,47].…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis included 5017 PWH who were reported to be using dolutegravir plus lamivudine. In 20 studies that reported data for sex, the majority of PWH treated with dolutegravir plus lamivudine were male (range, 60-97%) [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. In five of seven studies with reported racial demographics, C 90% of PWH were identified as White [30,32,33,42,43,46,47].…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Among studies that reported information on prior regimens (n = 1958), many PWH switched to dolutegravir plus lamivudine from 3DRs (n = 1718; 88%) [29,35,42,43,48,49,54,57]. Primary reasons for switching to dolutegravir plus lamivudine included toxicity of the previous regimen [48,52], avoidance of drug interactions [36,48,52,53], treatment regimen simplification [34,48,52,58], and comorbidities (including cardiovascular, renal, and bone disease) [34,53,58]. Of the comorbidities reported at baseline, bone, hypertension, liver, and metabolic comorbidities were most prevalent (Table 1) [32].…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-life data consistently report an overall excellent tolerability of DTG/3TC, with an absence/low incidence of toxicity [ 15 , 62 , 73 , 76 , 78 , 81 , 106 , 107 ], and improvements in CD4 count [ 62 , 73 , 76 , 78 ], CD4:CD8 ratio [ 62 , 74 , 78 , 107 ], and lipid profile [ 62 , 73 , 74 , 76 , 77 , 78 ], when DTG/3TC is used as initial or switch strategy. Patients begin to report significant improvements in symptom distress and treatment satisfaction after the first few months of initial treatment [ 15 ].…”
Section: Monitoring Of Treatment Safetymentioning
confidence: 99%
“…Interestingly, a recent case review reported no virologic failure in 25 patients who switched to DTG/dose-adjusted 3TC once daily, over a median time of 2.5 years of observation [ 106 ]. This proof-of-concept contributes to the provision of further confidence that simplification to once-a-day therapy with DTG and dose-adjusted 3TC may, in fact, be a viable solution in those patients with compromised renal functionality.…”
Section: Monitoring Of Treatment Safetymentioning
confidence: 99%